2016
DOI: 10.22211/cejem/65019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Energetic Additive Coated MgH2 on the Power of Emulsion Explosives Sensitized by Glass Microballoons

Abstract: Traditional emulsion explosives, in spite of excellent water resistance, safe handling and good storage performance, have low power problems which seriously hinders their use. In order to improve the power of emulsion explosives, a hydrogen based emulsion explosive was devised. Scanning electron microscope pictures and experimental storage results show that the coating effect and stability of coated magnesium hydride (MgH2) are very good. The power of an emulsion explosive sensitized by glass microballoons was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Table 6 shows that compared to GMs sensitized emulsion explosives, the shock wave attenuation time q, the shock wave specific impulse I and the shock wave total energy E of GMs-TiH 2 sensitized emulsion explosives in the underwater explosion experiments are increased 87.29 %, 18.50 % and 9.69 %, respectively. The experimental results of brisance of two kinds of emulsion explosives are somewhat in accordance with the mechanical impulse mechanism of brisance for explosives, which deems that the brisance parameter is related not only to the detonation pressure but also the shock wave duration [10]. Therefore, the reasons for the high brisance of the GM-TiH 2 sensitized emulsion explosives may be attributed to be the slower attenuation and the higher total energy of the shock waves.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Table 6 shows that compared to GMs sensitized emulsion explosives, the shock wave attenuation time q, the shock wave specific impulse I and the shock wave total energy E of GMs-TiH 2 sensitized emulsion explosives in the underwater explosion experiments are increased 87.29 %, 18.50 % and 9.69 %, respectively. The experimental results of brisance of two kinds of emulsion explosives are somewhat in accordance with the mechanical impulse mechanism of brisance for explosives, which deems that the brisance parameter is related not only to the detonation pressure but also the shock wave duration [10]. Therefore, the reasons for the high brisance of the GM-TiH 2 sensitized emulsion explosives may be attributed to be the slower attenuation and the higher total energy of the shock waves.…”
Section: Resultssupporting
confidence: 73%
“…In the early-stage, the MgH 2 powders were added to emulsion explosives as chemical sensitizers, and they would react with the emulsion matrix to produce gas bubbles to sensitize the emulsion matrix. The experiments results showed that MgH 2 powders could improve the explosion power [9,10] and the pressure-resisting ability [11][12][13] of emulsion explosives remarkably. But MgH 2 sensitized emulsion explosives may also have problems of foaming and safety for the hydrogen bubbles.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Energetic additives encapsulation is an effective way to improve the safety of high energy explosives, and various methods for coating energetic materials had been developed, including sol‐gel coating [15], crystal coating [16], spray drying coating [17] and in‐situ polymerization coating [18, 19]. However, there were many problems of traditional coating methods in ensuring the stability and the compatibility of energetic additives in emulsion explosives, for instance, poor coating effect and low strength of coating membrane [20].…”
Section: Introductionmentioning
confidence: 99%